The Role of the Palangka Raya City Government in Revitalizing Customary Law Values Based on the Huma Betang Philosophy - Hera Nugrahayu; Akhmad Husain (Jurnal Ilmu Hukum Tambun Bungai, 2025)
This study aims to examine the role of the Palangka Raya City Government in preserving customary law based on the Huma Betang philosophy, which represents the cultural identity of the Dayak community in Central Kalimantan. The research employs a normative legal approach using statutory, conceptual, and historical methods. Constitutionally, the preservation of customary law is guaranteed by Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia, which recognizes and respects indigenous law communities along with their traditional rights. At the regional level, the commitment to preserving local cultural values is affirmed through Central Kalimantan Provincial Regulation No. 1 of 2008 concerning Dayak Customary Institutions in Central Kalimantan, which serves as the legal foundation for involving customary institutions in regional development. The findings indicate that the Palangka Raya City Government has made efforts to integrate Huma Betang values into development policies and social life through support for customary institutions, cultural education programs, and preservation activities. However, challenges remain in terms of policy synchronization, comprehensive community involvement, and the internalization of cultural values amid the current of modernization. Strategic steps are needed through cross-sector collaboration and the strengthening of regional regulations to ensure the sustainability of customary legal values within an inclusive and sustainable development framework.